Pemanfaatan Aplikasi Akuntansi Berbasis Android untuk Meningkatkan Administrasi Keuangan pada UMKM Kedai Waramen - Ningrum, Maharani Sasmitha; Damayanty, Prisila; Siti Nurhayati; Al-Faruq, Huzaimah; Munir, Ahmad Musyaddad (PUAN INDONESIA, 2024)
The reason why MSMEs do not develop easily is because the accounting records of these MSMEs are weak. One of the factors is that MSME owners do not think about financial management and recording issues. Registered Financial Management Institutions will be able to help manage finances well. Some MSMEs believe that without accounting, their business can run smoothly and make a profit. This makes finances unclear and there will be losses and makes it difficult for MSMEs to find out their business capital.